PENINGKATKAN KEAKTIFAN ASPEK AFEKTIF SISWA DALAM PEMBELAJARAN GERAK DASAR LOMPAT TINGGI DENGAN METODE PERMAINAN SISWA KELAS IV SD NEGERI BANYURADEN GAMPING SLEMAN - Tri Ani Hastuti, Mulyaarja dan (Jurnal Pendidikan Jasmani Indonesia, 2016)
Abstract The research problem was that there were some fourth grade students of SD Negeri Banyuraden, Gamping, Sleman who found it hard to perform the high jump basic moves. The research objective was to improve the activeness of the affective aspects from the fourth grade students of SD Negeri Banyuraden, Gamping, Sleman on the high jump basic moves learning through the game method.This research was a classroom action research (CAR). The subjects were the fourth grade students of SD Negeri Banyuraden, Gamping, Sleman with the total of 26 students. The assessment instruments were such as the observation sheets assessment for the improvement of affective aspects activeness of the students. The research method consisted of four main aspects, such as planning, action, observation, and reflection. The data analysis was using descriptive qualitative and descriptive quantitative analysis. The indicator for thesuccess was when the assessment results for the improvement of the affective aspects activeness of the students in the high jump learningthrough the game method had been gaining a score at â‰¥ 51 in other words it means that an improvementfor the activeness of the affective aspects of the students was in "good".The results showed that it was proved that the meeting in two cycles had been able to improve the activeness of the affective aspects of the students in the high jump basic moves learning on the fourth grade students of SD Negeri Banyuraden, Gamping,Sleman. Significant improvement occurred as it was compared to the initial data and the data of the first cycle. Improvement for the activeness of the students’affective aspect in the high jump learning basic moves in the second cycle had the appropriate indicators of success. The score at "72" showed that the improvement for the activeness of the affective aspects of students was implemented really well. Keywords:Activeness, Affective, High Jump, Elementary School Students, Games Abstrak Permasalahan penelitian adalah terdapat beberapa siswa kelas IV SD Negeri Banyuraden KecamatanGamping Kabupaten Sleman yang sulit dalam melakukan gerak dasar lompat tinggi. Tujuan penelitian untuk meningkatkan keaktifan aspek afektif siswa dalam pembelajaran gerak dasar lompat tinggi siswa kelas IV SD Negeri Banyuraden Kecamatan Gamping Kabupaten Sleman dengan metode permainan. Penelitian ini merupakan penelitian tindakan kelas (PTK). Subyek penelitian adalah Siswa Kelas IV Banyuraden Kecamatan Gamping Kabupaten Sleman yang berjumlah keseluruhan 26 siswa. Instrumen penilaian berupa lembar observasi penilaian peningkatan keaktifan aspek afektif siswa. Metode penelitian tindakan kelas terdiri dari 4 aspek pokok, yaitu perencanaan, tindakan, tahap pengamatan/observasi, dan refleksi.Analisis data secara deskriptif kualitatif dan kuantitatif. Indikator pencapaian keberhasilan adalah apabila hasil penilaian peningkatan keaktifan aspek afektif siswa dalam pembelajaran lompat tinggi dengan metode permainan telah mendapatkan skor â‰¥ 51 dengan arti lain peningkatan keaktifan aspek afektif siswa berlangsung dengan "baik". Hasil penelitian menunjukkan terbukti bahwa kenyataannya dalam pertemuan di dua siklus sudah dapat meningkatkan keaktifan aspek afektif siswa dalam pembelajaran gerak dasar lompat tinggi siswa kelas IV SD Negeri Banyuraden Kecamatan Gamping Kabupaten. Peningkatan yang terjadi signifikan di bandingkan data awal dan data siklus satu. Peningkatan keaktifan siswa dalam pembelajaran gerak dasar lompat tinggi dalam ranah aspek afektif di siklus dua telah sesuai indikator keberhasilan. Skor "72" menunjukkan Peningkatan keaktifan aspek afektif siswa berlangsung dengan baik. Kata kunci : Keaktifan, Afektif, Lompat Tinggi, Siswa SD, Permainan